Helicobacter Pylori Infection in Canada’s Arctic: Searching for the Solutions - Justin Cheung; Karen Goodman; Rachel Munday; Karen Heavner; Janis Huntington; John Morse; Sander Veldhuyzen van Zanten; Richard N Fedorak; Andre Corriveau; Robert J Bailey; for the CANHelp working group (Canadian Journal of Gastroenterology)
The Canadian North Helicobacter pylori (CANHelp) working group is a team composed of investigators, health officials and community leaders from Alberta and the Northwest Territories. The group’s initial goals are to investigate the impact of H pylori infection on Canada’s Arctic communities; subsequent goals include identifying treatment strategies that are effective in this region and developing recommendations for health policy aimed at management of H pylori infection. The team’s investigations have begun with the Aklavik H pylori Project in the Aboriginal community of Aklavik, Northwest Territories.